Inequalities in access to healthcare by local policy model among newly arrived refugees: evidence from population-based studies in two German states - Wenner, Judith; Biddle, Louise; Gottlieb, Nora; Bozorgmehr, Kayvan (International journal for equity in health, 2022)
Access to healthcare is restricted for newly arriving asylum seekers and refugees (ASR) in many receiving countries, which may lead to inequalities in health. In Germany, regular access and full entitlement to healthcare (equivalent to statutory health insurance, SHI) is only granted after a waiting time of 18 months. During this time of restricted entitlements, local authorities implement different access models to regulate asylum seekers’ access to healthcare: the electronic health card (EHC) or the healthcare voucher (HV). This paper examines inequalities in access to healthcare by comparing healthcare utilization by ASR under the terms of different local models (i.e., regular access equivalent to SHI, EHC, and HV).